Habitat use by banded kokopu (Galaxias fasciatus) and giant kokopu (G. argenteus) co‐occurring in streams draining the Hakarimata Range, New Zealand - Cindy F. Baker; Joshua P. Smith (New Zealand Journal of Marine and Freshwater Research, 2007)
Habitat selection by banded kokopu (Galaxias fasciatus) and giant kokopu (G. argenteus) was examined in three first‐ and second‐order restored streams draining the Hakarimata Range, Waikato region, New Zealand. Longitudinal distribution surveys were undertaken recording physical habitat dimensions and cover selection at the location of each banded and giant kokopu. The main habitats used by both species were pools or backwaters, and both species strongly selected debris dams and undercut banks over other types of in‐stream cover. The key features discriminating banded kokopu and giant kokopu habitat were elevation, habitat size, and riparian cover. Banded kokopu were found at higher elevations than giant kokopu, where habitats had smaller dimensions and higher proportions of native bush as riparian cover. Within the study streams, in‐stream debris, in the form of debris dams, was strongly selected as cover by both species and therefore could be an important feature in habitat restoration within the Waikato region, especially in streams where undercut bank cover is scarce.